A Prospect of Digital Airborne Photogrammetry Approach for Cadastral Mapping in Nepal - Tamrakar, Rabindra Man (Journal on Geoinformatics, Nepal, 2012)
Although the history of land recording system is very old in Nepal, systemic cadastral survey was commenced only after the promulgation of Land Measurement Acts in 1963 and the implementation of land reform programme in 1964. Cadastral survey of all 75 districts of Nepal was completed in 1995/96 using traditional graphical method with plane tables and telescopic/plane alidades. Derived information from the existing maps now are outdated and do not fulfill the needs of the general public. 27 out of the 83 district survey offices under Survey Department, Government of Nepal are presently involved in cadastral mapping of the village block areas which previously have been left out in the first phase of surveys (1964-1996). These offices as well are engaged in the preparation of new mapping series of the districts using the same traditional graphical survey method. The speed of this survey is relatively slow and the general public also is not very satisfied with this resurveying method. People now are soliciting for updated and reliable land information based on new cadastral maps due to greater demand for land market and higher land values. Now the time has come to adopt an appropriate innovative approach for resurveying in the country in order to meet the growing public demands on reliable land information system as well as to provide prompt services. Although various technologies in cadastral mapping are currently available, digital airborne photogrammetry using aerial photographs probably could be an appropriate technology for resurveying in Nepal, especially in the hilly districts for developing accurate and reliable land information system.